The changing pattern of toxicity of digoxin. - Henry, D. A. (BMJ Group, 1981)
Toxicity to digoxin was monitored in 437 consecutive recipients in a comprehensive drug surveillance programme, Adverse reactions developed in 19.5% and, in contrast to previous reports, were generally of a relatively benign nature. There were no drug-related deaths, but patients with adverse reactions spent longer in hospital. Low body weight, impaired renal function, old age and concurrent use of diuretics individually did not increase the risk of toxicity. This was attributed to improvements in the prescribing of digoxin. There was a highly significant excess of gastrointestinal reactions in women, which tended to occur early in the course of therapy. This susceptibility is not widely recognized. The use of loading doses may have caused many early reactions and it is suggested that this practice cold be abandoned in all but the most urgent cases.